Legal Mechanisms for the Protection of Children’s Rights in the Family - Ubaidullaeva Fatima (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This paper briefly and clearly explains children’s rights within the family, including the right to education, protection, upbringing, and their importance for the child. In addition, the study examines legal mechanisms for protecting children’s rights in the family and analyzes the responsibilities of parents in ensuring and safeguarding these rights. The purpose of the work is to outline children’s rights using the legislation of the Republic of Uzbekistan and to provide examples of practical measures implemented in the country to protect children’s rights in the family. The research primarily employs analytical and systematic research methods. Special attention is paid to the problems of violations of children’s rights and the mechanisms for their protection. As a result, the study concludes that it is necessary to familiarize children with the rights they enjoy within the family and society, as well as to strengthen parental responsibility and control over the observance of children’s rights.